Morphometric characteristics of the umbilical cord and vessels in fetal growth restriction and pre-eclampsia. (January 2016) - Sharony, Reuven; Keltz, Eran; Biron-Shental, Tal; Kidron, Debora
Abstract: Background: Reports on the morphometric analysis of umbilical cord (UC) and its vessels have been inconsistent due to varying inclusion criteria and methodology. The current study tried to overcome the limitations of previous studies by comparing the UC in pregnancies complicated by fetal growth restriction (FGR), preeclampsia (PE) and FGR + PE, to healthy controls. Aims: Analyze the morphometric attributes of the UC in pregnancies complicated by FGR and PE. Study design: Case–control. Subjects: The study groups consisted of 36 patients with FGR + PE, 72 with FGR (without PE) and 15 with PE (without FGR). They were compared to 50 patients without FGR or PE. Outcome measures: Histological cross-sections of the UC were photographed and measured. The following variables were recorded: cross-section area of UC, thickness and surface area of umbilical vessel walls, shortest distance between cord surface and nearest artery (DSA), distance between the arteries (DBA) and placental weight and measurements. The area of the Wharton's jelly (WJ) area was calculated. Results: UC and WJ cross-section areas were significantly smaller in FGR + PE and FGR, but not in PE. The umbilical vessel wall area was decreased in FGR + PE, but the thickness was not significantly decreased in all three study groups, compared to controls. DSA was smaller in all three groups, whereas DBA was not significantly different, compared to controls. Conclusions: Smaller UC cross-section areas were seen in FGR and FGR + PE, but not in PE without FGR. However, there is no evidence to determine whether this reduction is a cause or consequence of FGR. Reduced DSA in PE, whose UC cross-section area was not smaller as in FGR and FGR + PE, might reflect alterations in UC induced by PE. Highlights: Umbilical cord area was smaller in fetal growth retardation + preeclampsia. The cord area was smaller in fetal growth retardation, but not in preeclampsia. The vessel wall area was smaller only in fetal growth retardation + preeclampsia. Distance of cord surface to artery was smaller in all 3 study groups than in controls.